The Influence Of Financial Literacy, Financal Inclusion and Fintech Payment Development On The Performance Of MSMEs In Pare District - Betari, Dinda Dwi Putri; Puspita, Erna; Kurniawan, Andy (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research Objective: The growth of MSMEs is very rapid every year, where the rapid growth of MSMEs, business owners need to increase their knowledge in finance, utilize financial institutions as a tool for business development and also need to keep up with growing technological growth. So this study aims to find out about the effect of financial literacy, financial inclusion and the development of fintech payments on the performance of MSMEs in Pare. Research Method: This study uses an associative quantitative approach with a sample of 90 MSMEs engaged in the food and beverage sector and using fintech payments in Pare District. Samples will be collected by distributing questionnaires to informants with various terminals that have been tested for validity and reliability. Then to test it using multiple linear regression test with the SPSS application. And the acquisition of research results showing that financial literacy, financial inclusion and the development of fintech payments have a positive influence on the performance of MSMEs. Research Finding: The results of this study state that the performance of MSMEs is influenced by financial literacy, financial inclusion and the development of fintech payments.